ANALISIS FAKTOR PENENTU PERUSAHAAN DI INDONESIA MELAKUKAN PINJAMAN KE LUAR NEGERI - Doni Satria (Universitas Negeri Padang, 2013)
Why a firm issuing the global bonds? This is the question I try to investigate in this research. This phenomena is worth to investigate since from our 1997//98 crisis experience, high exchange rate depreciation triggered the external debt accumulation in Indonesia. This process ends up with an economic malaise, and many firm become highly indebted or collapse. After the beginning of global economic crisis in 2007, the trend of global bonds issuance by Indonesian corporation has the same pattern with the pre 1997/98 Asian crisis. Using OLS regression analysis due to the limitation of data availability, I found: the Indonesian corporate sector is more prudent in issuing global bonds, since the auto hedging is one of the significance factor. The decision in issuing global bonds are also depends on lower cost of fund and the availability of fund in domestic market. I conclude that recent global bonds issuance trend by Indonesian corporate sector is not a threat for Indonesian economy.